(untitled) - Demouy, Valérie (London, 2007)
This new and entirely revised edition of Colloquial Frenchis easy to use and completely up-to-date! Specially written by an experienced teacher for self-study or classroom use, the course offers you a step-by-step approach to written and spoken French. No prior knowledge of the language is required. What makesColloquial French,3rd edition your best choice in personal Language Learning? - interactive - lots of exercises for regular practice, focussing on up-to-date everyday language - clear - concise grammar notes - practical - useful vocabulary and simplified pronunciation guide - complete - including answer key, reference grammar, glossary and index By the end of this rewarding course you will be able to communicate confidently and effectively in French in a broad range of everyday situation. Two 60-minute cassettes or CDs are available to complement the book. Recorded by native speakers of French, this material will help develop your listeningand pronunciation skills.
Keywords: French language,French language-Spoken French.,Ngôn ngữ Pháp; Conversation and phrase books-English